Rhyacophilidae - Küçükbasmaci, İbrahým; Canbulat, Savaş (Zenodo, 2020)
Family Rhyacophilidae Himalopsyche gigantea (Martynov 1914) —Range: China, Kazakhstan, Tadzhikistan, and Kyrgyzstan (Huang et al. 2005; Iva-nov 1994; Lepneva 1964; Morse 2020; Smirnova et al. 2016). Himalopsyche kuldschensis (Ulmer 1927) —Range: China (Tibet) and Kyrgyzstan (Malicky & Chantaramongkol 2000; Yang et al. 2005). Rhyacophila extensa Martynov 1928 a—Range: Pakistan, India, Nepal, Kazakhstan, and Kyrgyzstan (Kiss 2013; Morse 2020; Oláh 1994; Saini et al. 2001; Smirnova et al. 2016)

Published as part of Küçükbasmaci, İbrahým & Canbulat, Savaş, 2020, A List of the Caddisflies (Insecta: Trichoptera) from Kyrgyzstan, with a New Record (Triaenodes reuteri McLachlan 1880), pp. 113-122 in Zootaxa 4896 (1) on page 114, DOI: 10.11646/zootaxa.4896.1.6, http://zenodo.org/record/4359410
Keywords: Insecta; Arthropoda; Trichoptera; Animalia; Rhyacophilidae; Biodiversity; Taxonomy